THE IMPLEMENTATION STUDY OF STORING AND REPORTING OF NARCOTICS AND PSYCHOTROPICS AT PHARMACIES IN DENPASAR CITY, BALI PROVINCE - Putra Nugraha, Arie Dharma; Hendra, Kadek; Gelgel Wirasuta, I Made Agus (Journal Pharmaceutical Science and Application; Vol 3 No 1 (2021): Journal Pharmaceutical Science and ApplicationDO - 10.24843/JPSA.2021.v03.i01.p02, 2021)
Introduction: Storage and reports of narcotics and psychotropics in pharmacy must be carried out according to standard operating procedures which are based on legislation on maintaining safety, efficacy, and quality of the drugs. Objective: This study aimed to observe the implementation process of narcotics and psychotropic storing and reporting in accordance to the law in force in several pharmacies in Denpasar City. Methods: Five biggest pharmacies located in Denpasar City were picked by a purposive sampling method. This study used a descriptive observational method to provide a brief overview of the term and condition of narcotics and psychotropic storing and reporting that implemented in real-time in the pharmacies. Results: Overall, the study revealed that the majority of pharmacies were successfully in term of fulfilling the various aspects of narcotics and psychotropic storing and reporting, including the storage of drugs at the special cabinets, in special the implementation process of narcotics and psychotropic that cited in the Regulation of The Minister of Health of the Republic of Indonesia Number 73 of conditions according to safety and stability, FEFO and FIFO systems, manual and electronic stock cards system, separation of damaged and/or expired drug, inventory stock, and compliance and completeness of reporting using SIPNAP. Conclusion: Responsible pharmacist must always evaluate the storage and reporting of narcotics and psychotropic in the pharmacy to guarantee quality and maintain suitability of the pharmaceutical services process according to established standards. Keywords: forensic pharmacy, storing and reporting, narcotics and psychotropic, legislation